Hardness evaluation of prosthetic silicones containing opacifiers following chemical disinfection and accelerated aging - Marcelo Coelho Goiato; Marcela Filié Haddad; Daniela Micheline dos Santos; Aldiéris Alves Pesqueira; Amália Moreno (Sociedade Brasileira de Pesquisa Odontológica, 2010)
We evaluated the effects of disinfection and aging on the hardness of silicones containing opacifiers and intended for use in facial prosthetics. A total of 90 samples were produced using a cylindrical metal mold 3 mm in height and 30 mm in diameter. The samples were fabricated from Silastic MDX 4-4210 silicone in three groups: GI contained no opacifier, GII contained barium sulfate (Ba), and GIII contained titanium dioxide (Ti). The samples were disinfected using effervescent tablets (Ef), neutral soap (Ns), or 4% chlorhexidine (Cl) 3 times a week for 60 days. After this period the samples underwent 1,008 hours of accelerated aging. The hardness was measured using a durometer immediately following the disinfection period and after 252, 504, and 1,008 hours of aging. The data were statistically analyzed using 3-way ANOVA and the Tukey test (p < .05). The GIII group exhibited the greatest variation in hardness regardless of elapsed time. All groups displayed greater hardness after 1,008 hours of accelerated aging independent of disinfectant type. All of the hardness values were within the clinically acceptable range.